2019
DOI: 10.1007/s00259-019-04481-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of FDG-PET/CT of post-transplant lymphoproliferative disorder and factors affecting diagnostic yield

Abstract: Purpose Post-transplant lymphoproliferative disorder (PTLD) is a serious complication after solid organ and hematopoietic stem cell transplantation, requiring a timely and accurate diagnosis. In this study, we evaluated the diagnostic performance of FDG-PET/CT in patients with suspected PTLD and examined if lactate dehydrogenase (LDH) levels, Epstein-Barr virus (EBV) load, or timing of FDG-PET/CT relate to detection performance of FDG-PET/CT. Methods This retrospective study included 91 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…Among the main clinical features, only increased lactate dehydrogenase levels seemed to be correlated with a true positive 18 F-FDG PET/CT scan in PTLD patients. EBV-DNA load and timing of 18 F-FDG PET/CT after transplantation did not affect the diagnostic performance of 18 F-FDG PET/CT in PTLD [5]. The good diagnostic performance reported in this study suggests that 18 F-FDG PET/CT is a valuable imaging modality for detecting PTLD.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Among the main clinical features, only increased lactate dehydrogenase levels seemed to be correlated with a true positive 18 F-FDG PET/CT scan in PTLD patients. EBV-DNA load and timing of 18 F-FDG PET/CT after transplantation did not affect the diagnostic performance of 18 F-FDG PET/CT in PTLD [5]. The good diagnostic performance reported in this study suggests that 18 F-FDG PET/CT is a valuable imaging modality for detecting PTLD.…”
mentioning
confidence: 53%
“…The article of Montes de Jesus et al recently published in EJNMMI provides further evidence on the usefulness of 18 F-FDG PET/CT in the management of patients with PTLD [5]. In this retrospective study, the authors evaluated the diagnostic performance of 18 F-FDG PET/CT in a significant population (n = 91) of patients with suspected PTLD examining the factors affecting the diagnostic yield of 18 F-FDG PET/CT.…”
mentioning
confidence: 99%
“…No additional records were found screening the references of these articles. Therefore, five studies were included in the qualitative analysis (systematic review) and in the quantitative analysis (meta-analysis) [12][13][14][15][16].…”
Section: Literature Searchmentioning
confidence: 99%
“…The characteristics of the studies included in the systematic review are presented in Tables 1-4, whereas the overall quality assessment of the studies included in the meta-analysis is reported in Figure 2. Screening the selected databases, five articles evaluating the diagnostic performance of 18 F-FDG PET or PET/CT for detection of PTLD in 336 transplant recipients were selected (Table 1) [12][13][14][15][16]. All the selected articles were retrospective single-centre studies published from 2009 to 2019 by research groups from different countries, mainly from Europe.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation